A rare case of indirect inguinal hernia with ovary as content at a hospital of Visakhapatnam (Indian Journal of Case Reports, 2018)
A hernia is the protrusion of the small intestines or omentum or other organs through a defect in the abdominal wall. Inguinal hernia in females is very rare and occurs in <5% of women. Here, we report the case of a 25-year-old female who presented with swelling in the left groin associated with dragging pain in the left iliac fossa. She was investigated and diagnosed as a left indirect inguinal hernia. Hernioplasty was planned and intraoperatively ovary along with fimbria was identified as content. An inguinal ovary may occur if the gubernaculum fails to attach to the uterus in fetal life or if the canal of Nuck remains open after birth.